SELF-IDENTIFICATION FACTORS OF VISITORS TO THE MEMORIAL LANDSCAPE OF THE ARKAIM ARCHAEOLOGICAL SITE - Andrey V. Safonov; Irina V. Topchii (Russian Studies in Culture and Society)
The article uses the case of Arkaim archaeological site in Chelyabinsk Region to unravel the mechanisms of building a connective structure that determine the strategies for self-identification of various groups of actors in this memorial landscape. The term “connective structure” is used in the meaning assigned to it by Jan Assmann, creator of the concept of communicative and cultural memory that is central to this study. Contributors to the article also rely on the theory of historical and collective memory proposed by Maurice Halbwachs. The connective structure of Arkaim is explored as a multidimensional phenomenon whose conceptual facets are represented by the natural landscape and its history, the history of Arkaim settlement dating back to the Bronze Age, the historical facts, legends and tales, as well as the history of discovery and promotion of this archaeological monument. Extensive interviews with actors are used to single out the four key factors of self-identification: territorial, professional, cultural, and personal. The article describes how each of these factors manifests itself in relation to the features of the memorial landscape.